THE USE OF AUDIO VISUALMEDIA IN IMPROVING STUDENTS' NEWS LEARNING CLASS XI SMA NEGERI 7 WAJO - Nur Fadilah; Nurmia Muin; Andi Puspitasari (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research is to improve students' news listening learning, the use of audio visual media in learning can improve the expected thinking abilities of class XI students at SMA Negeri 7 Wajo. This type of research is Classroom Action Research (PTK). Classroom action research seeks to improve the quality of research objects and problem solving by observing the success and results of actions and adding additional information that can encourage better behavior or change conditions and situations with more desirable results. In the pre-cycle the average student score was 61 and 4 people reached the KKTP or 14%. In cycle 1 the average student score was 71 and 15 people achieved the KKTP or 52%. The average score of students in cycle 2 increased by 82 and 27 students reaching the KKTP or 93%. Based on the results of the research and discussion above, it can be concluded that the use of audio visual media can improve learning to listen to the news in class XI IPS 2 students at SMA Negeri 7 Wajo. Research conducted during the pre-cycle stage to cycle 2 showed different results. Where every cycle there is an increase in students' learning to listen to the news.